The advanced lung cancer inflammation index predicts outcomes in patients with Crohn's disease after surgical resection. (11th August 2020) - Kusunoki, K.; Toiyama, Y.; Okugawa, Y.; Yamamoto, A.; Omura, Y.; Kusunoki, Y.; Yin, C.; Kondo, S.; Okita, Y.; Ohi, M.; Sasaki, H.; Bando, T.; et al.
Abstract: Aim: Precise biomarkers for predicting prognosis could help to identify high‐risk Crohn's disease (CD) patients to facilitate better follow‐up during the postoperative course. In this study, the primary aim is the identification of the most reliable nutrition marker that predicts surgical relapse in CD patients. Method: We first evaluated the predictive value of various nutrition markers for postoperative surgical relapse in CD patients and identified the advanced lung cancer inflammation index (ALI) as a promising biomarker. Then, we assessed the clinical significance of preoperative ALI in CD patients using two cohorts. Results: Preoperative ALI showed the highest correlation with reoperation rate compared with other nutritional parameters in CD patients receiving surgical resection (sensitivity 53%, specificity 86%, area under the curve 0.71). Lower levels of preoperative ALI were significantly correlated with the presence of perianal disease. A lower level of preoperative ALI was an independent prognostic factor for reoperation rate after an intestinal resection (hazard ratio 3.37, 95% CI 1.38–10.12, P  = 0.006), and the prognostic impact of preoperative ALI was successfully validated in an independent cohort using the same cut‐off value. Conclusion: Preoperative ALI might be useful for postoperative management of CD patients.